Estrone – a partial estradiol antagonist in the normal breast. (2nd September 2015) - Lundström, Eva; Conner, Peter; Naessén, Sabine; Löfgren, Lars; Carlström, Kjell; Söderqvist, Gunnar
Abstract: Oral hormone replacement therapy (HRT) based on estradiol-17β (E2) greatly increases circulating estrone (E1) levels. E1 is an estrogen receptor agonist but may also be a partial E2 antagonist. We investigated the effects of circulating E1 on the association between circulating E2 and the increase in mammographic density (∂MD) in 46 healthy post-menopausal women treated with E2 2 mg and norethisterone acetate 1 mg daily. MD and serum E1 and E2 were measured before and after 6 months of treatment. At high E1 levels, ∂MD showed significant positive correlations leading to increase (∂-values) in both E1 and E2. Lowering the upper serum E1 limit strengthened the correlations to ∂E2 while the significant correlations to ∂E1 disappeared. E1 at high concentrations may act as a partial E2 antagonist also in the normal breast in vivo and disturb relationships between circulating E2 and biological estrogen effects. When investigating the relations between circulating steroids and their effects, structurally related compounds, which may act as partial antagonists, have to be considered, at least when they are present in higher concentrations. Chinese abstract: 口服激素替代治疗（HRT）基于17β-雌二醇（E2）大大增加了循环的雌酮（E1）的水平。E1是一种雌激素受体激动剂，但也可能是一个E2的部分拮抗剂。我们研究了46名健康绝经后女性每天口服E2 2mg和醋酸炔诺酮1mg后循环中E1在循环中E2与乳腺密度增加之间关系中的作用。治疗前和治疗6个月后分别测定乳腺密度及血清E1和E2。E1高水平时，乳腺密度与E1和E2的增加呈密切正相关。不断降低血清E1至上限，与E2的相关性加强而与E1的相关性消失。E1在高浓度时可能是体内正常乳腺组织内E2的部分拮抗剂，干扰了循环中E2和雌激素生物效应之间的联系。当研究循环中类固醇和它们作用的时候，结构相关的化合物具有较高浓度的时候必须要考虑，因为它们可能是部分拮抗剂。